A study of the genetic diversity in the Heze Han population using a novel genotyping system based on 24 Y-chromosomal STR loci. (December 2017) - Li, Min; Que, Tingzhi; Huang, Lei; Chen, Yuling; Li, Yanan; Jiang, Lei; Zhu, Ruxin; Zhou, Wei; Bian, Yingnan; Li, Chengtao
Abstract: We established a 24-plex Y-STR typing system by including the 13 Y-STR loci used in AmpFLSTR ® Yfiler ® PCR Amplification Kit (Applied Biosystems, Foster City, CA) and 11 additionally selected Y-STR loci that significantly increased power of discrimiation. We applied the system to genotype 195 unrelated Chinese Han males, resulting in 195 distinct haplotypes. The diversity observed across loci ranged from 0.0885 (DYS645) to 0.9646 (DYS385a/b)., while the haplotype diversity was 1 based on the 24 Y-STR loci. The ultra-high differentiation power of the genotyping system has great potential in forensic applications.